(untitled) (Medico Legal Update, 2021)
A 10-year-old male patient presented with Severe Late Crouzon Syndrome, with turri-brachycephaly, and severe exorbitism of both eyes, visual loss, beaked nose and maxilla hypoplasia. The head circumference was 54 cm and 90 precentile. Patient had a high arched palate, tonsil hypertrophy and type III malocclusion. From the multidisciplinary meeting, in the first stage it was decided to first secure the airway with Tracheostomy then immediately followed by Monobloc Advancement with External Frontofacial Distraction. Then in the second stage, after removal of the rigid external distractor, by 9 months after first surgery, the patient underwent a simultaneous procedures of Adenoidectomy, Conchotomy, and Septoplasty. Thus, after patient got stable in follow-up, Nasendoscopy and Tracheostomy devices was removed. After 11 months follow-up. Visual function still not getting better. However turri-brachycephaly, exorbitism of both eyes, beaked nose and maxilla hypoplasia, head circumference, arched palate, tonsil hypertrophy and the malocclusion were getting much reduced, and the patient getting happier and more active.